1987
DOI: 10.1128/iai.55.4.1009-1013.1987
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of specific DNA sequences among pathogenic and commensal Neisseria species

Abstract: Several traits, including pili and the outer membrane proteins P.11 and H.8, have been associated with pathogenic Neisseria species. We examined several Neisseria species for DNA sequence homology to cloned pilin, P.11, and H.8 genes. Strains of Neisseria gonorrhoeae and N. meningitidis showed hybridization to all of these genes. Commensal strains showed little hybridization to any of these genes. Strains of N. lactamica and N. cinerea showed intermediate patterns of hybridization. Generally, organisms that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…The pilS and pilE probes did not hybridize with commensal Neisseria species (a possible exception was a weak signal seen with pits and N. subflava). a finding noted previously (Aho and Cannon, 1987). Thus, in commensal strains, FKBP genes were not linked to known pilin loci.…”
Section: Location Of Fkbp-like Genes In the Meningococcal And Commenssupporting
confidence: 70%
“…The pilS and pilE probes did not hybridize with commensal Neisseria species (a possible exception was a weak signal seen with pits and N. subflava). a finding noted previously (Aho and Cannon, 1987). Thus, in commensal strains, FKBP genes were not linked to known pilin loci.…”
Section: Location Of Fkbp-like Genes In the Meningococcal And Commenssupporting
confidence: 70%
“…Western blotting of whole cell lysates of commensal strains using the mAb B33 raised against pathogenic Opa protein demonstrated the expression of Opa proteins by all of the Cn tested. In earlier studies, the presence of opa genes in various commensal isolates was observed, but their expression was not detected (Aho et al, 1987;Wolff and Stern, 1995).…”
Section: Discussionmentioning
confidence: 88%
“…To date, studies on Cn have indicated that, in general, they have a limited repertoire of pathogenic determinants. Studies on 12 commensal neisserial strains failed to detect opc-like genes (Zhu et al, 1999), whereas pilin genes have been detected in several human commensal neisserial isolates tested (Aho et al, 1987). Commensal genes homologous to pathogenic neisserial opa have been identified in previous studies, but their expression was not detected (Wolff and Stern, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…However, more detailed investigations imply that some of these factors are more widely distributed. Pili, a well known virulence factor in gonococcal and meningococcal infection, have also been observed on commensal Neisseria species [2]. The opacity protein (Opal, an outer membrane protein of gonococci, seem to have an equivalent in meningococci, formerly designated as class 5 proteins.…”
Section: Introductionmentioning
confidence: 99%